Molecular study of Pompe disease in Egyptian infants - Mona Essawi (SpringerOpen, 2021)
Abstract Background Pompe disease (PD) is a serious genetic disorder caused by deficiency of acid α-glucosidase (GAA) and subsequent glycogen accumulation inside lysosomes. This study included a cohort of 5 Egyptian infants (1–8 months old) with far lower than average normal GAA activity and clinical signs of PD in 4 of the 5 cases. The fifth case was discovered by newborn screening (NBS). Molecular analysis of the GAA gene was performed to confirm the diagnosis and identify the underlying mutation. Results The study identified the causative mutations [c.1193T > C (p.Leu398Pro), c.1134C > G (p.Tyr378*) & c.1431del (p.Ile477Metfs*43)] in 4 cases. However, molecular analysis reversed the expected pathologic state in the fifth infant, where his reduced enzymatic activity was related to the presence of pseudodeficiency allele c.868A > G (p.Asn290Asp) in addition to heterozygous disease-causing mutation c.2238G > C (p.Trp746Cys). Conclusion This study presents the first molecular analysis of GAA gene in Egypt and has thrown some light on the importance of PD molecular diagnosis to provide precise diagnosis and enable therapeutic commencement in affected subjects.